Repetitive Late Pleistocene soft‐sediment deformation by seismicity‐induced liquefaction in north‐western Lithuania. Issue 7 (26th May 2021) - Belzyt, Szymon; Pisarska‐Jamroży, Małgorzata; Bitinas, Albertas; Woronko, Barbara; Phillips, Emrys R.; Piotrowski, Jan A.; Jusienė, Asta
Abstract: Liquefaction can cause deformation of unconsolidated sediment, but specific processes involved and the trigger mechanisms often remain obscured. This study describes multiple deformed sediment layers in a succession of lacustrine sand, silt and clay deposited during the Marine Isotope Stage 5d in north‐western Lithuania. The deformation structures (load casts, pseudonodules, ball‐and‐pillow structures, broken‐up laminae and injections) are embedded in ten separate layers of fine‐grained, laterally continuous sediments. Detailed mesoscale sedimentological analyses suggest that each deformation event consisted of numerous successive stages of sediment advection facilitated by liquefaction. Low‐permeability fine‐grained laminae contributed to localized pore‐water pressure build‐up and lowering of sediment strength. Erosional top surfaces that truncate layers with soft‐sediment deformation structures suggest that at least seven deformation events were separated by successive periods of initial erosion and then uninterrupted deposition in the lake. The most likely trigger of the deformation was recurrent palaeoseismic activity possibly linked to a late glacial isostatic adjustment following the Scandinavian Ice Sheet melting after the Saalian glaciation. This study emphasizes the potential role of seismic processes in shaping the sedimentary record of the intraplate region of north‐eastern Europe and contributes to constraining the depth of liquefaction, regardless of the actual trigger mechanism.